Analyzing Population Density Gradient in Asansol City, West Bengal - Maji, Suvra; Alam, Sarfaraz (National Geographical Journal of India, 2022)
Though urban centres represent spaces of high population clusters, yet they show variations in spatial patterns of their population density. An understanding of the dynamics of spatial pattern of urban population density can provide deep insight about their social-spatial structure as well as their spatial policy and planning requirements. The urban density gradient is an important model for mapping and measuring urban population density. It has also been profitably used for predicting changes in the spatial pattern of population density within an individual city, which through light on the shifting functional importance of different parts of the city. On the basis of 2001 and 2011 Indian Census data, the paper maps and measures changes in spatial patterns and lapse rate of population density across 50 wards of Asansol city of West Bengal, India. The study point towards the straightening of the concave shape slope of population density gradient due to increase in population density of wards located adjacent to the centre of the city. It also indicates towards the emergence of multi-centered population density peaks within the municipal boundary of the city. Finally, the study points out that the future population growth is expected to take place in wards surrounding the centre of the city in view of relatively low population density. The study correlates changes in population density with ward-level changes in population engaged in various economic activities during the same time interval. Finally, it suggests that, even though changes in population density in the city exhibit explicit spatial patterns, there is no evidence to suggest that these changes have taken place in response to planned territorial development of the city.